New approaches to synthesis and applications of layered double hydroxides containing functional cations - Vieira, Daniel Eduardo Loureiro (2022)
This PhD work focuses on developing new multifunctional materials based on chemically and nanostructurally modified layered double hydroxides (LDH). LDH are mainly considered as anion exchangers regardless of their cation content. The central idea is the introduction of selected cations that can extend the functionalities of LDH and induce new properties, namely magnetic cations to assist thin-film formation and cations with inhibiting corrosion properties. LDH allow several modification levels by employing ion ordering and nanostructure design. Depending on the combination of properties, such materials can either serve as the object of fundamental research or find applications as a base for sensing/protective coatings. In this work, the conventional synthesis techniques were improved by the application of high-power ultrasound that resulted in a considerable acceleration of the crystallization process and the anion-exchange reaction. The magnetic behaviour of ConAl LDH intercalated with nitrate was studied as a function of temperature. The results obtained demonstrate that the magnetic properties of Co-based LDH strongly depend on the four lowest Kramer doublets. The appearance of a local maximum in the magnetic susceptibility at a temperature of 160 K is due to the freezing of the lattice parameters, and the curve's behaviour can be described by a non-linear change of the effective nuclear charge change of Coᴵᴵ. Following the magnetic characterization, the sedimentation of nanocrystallites of Co-Al LDH in magnetic fields perpendicular and parallel to the substrate was studied. Dense and homogeneous films were obtained for a magnetic field of 0.5 T applied perpendicularly to the sample. The magnetic anisotropy of the crystallites is explained by deviation from the statistical cation distribution similar to honeycomb-like coordination of cobalt. In a parallel study, cerium cations, which possess corrosion protection capacity, were incorporated in the LDH structure via partial substitution of aluminium cations. The changes occurring to the LDH in suspension after exposure for an extended period to UV radiation and its effect on the corrosion protection were evaluated. The last part of this work was devoted to the effect of magnetic fields on the anion-exchange of Co₂Al LDH and Co₃Al LDH for fields of 0, 0.25, 0.5, 0.75 and 1 T.